Flow cytometry for minimal residual disease testing in acute leukemia: opportunities and challenges. (2nd September 2018) - Gaipa, Giuseppe; Buracchi, Chiara; Biondi, A
ABSTRACT: Introduction : Flow cytometric quantification of minimal residual disease (MRD) in acute leukemia (AL) represents an indispensable tool to guide modern therapeutic protocols toward a precision medicine approach, being a powerful predictor of the overall response to treatment. This review covers the most challenging aspects and developments of this method, aiming at supporting further its implementation in clinical practices. Area covered : Flow cytometric MRD is based on the discrimination of leukemia cells from their physiological counterparts by the recognition of the leukemia-associated immunophenotypes. Technical and standardization advances along the last decades have been implemented allowing flow cytometric MRD to consolidate its role in modern therapeutic protocols for ALs. However, gaps in sensitivity and data interpretation are still present together with the need for further optimization of MRD-based clinical protocols. In this review, we critically analyze and discuss the most relevant and representative contributions in the field by accurate selection of the literature available in PubMed. Expert commentary : Further research in flow cytometric MRD can bring this technology toward wider and consistent applications in multiple acute leukemia settings rendering this tool a future golden standard and providing clinicians with more reliable and accurate tools for clinical decisions.